Administracja publiczna pod rządami prawa zamówień publicznych - Guziński, Maciej (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the implementation of public tasks in the public contract public administration entities perform different roles, in accordance with the provisions of the Public Procurement Act. There are in the process of public procurement as a contracting entity – the entity awarding of public contracts. As a contractor – the entity applying for the awarding. President of the Public Procurement Office as an authority acts as an entity controls the award of the contract.
Keywords: the contracting authority; the inspection body; public procurement; public administration; the contractor